Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species - Tang, Chufei; Wang, Ning; Yang, Ding (Zootaxa, 2016)
There are 26 species of Rhaphium recorded from China, including the following six species described as new to science: Rhaphium apophysatum sp. nov., R. bilobum sp. nov., R. bisectum sp. nov., R. daqinggouense sp. nov., R. dorsiseta sp. nov., R. neimengense sp. nov. Two new groups: the R. flavilabre and R. bilobum species groups are proposed. A key to the species of Rhaphium from China is provided.